Pagan light dreams of freedom and beauty in Capri - James, Jamie 1951-2020 (Farrar, Straus and Giroux, 2019)
"A history of the artists and renegades who found refuge on the island of Capri"--
Keywords: Sozialgeschichte; Schriftsteller; Künstler; Exil; Capri; Capri Island (Italy) / History; Capri Island (Italy) / Intellectual life; Expatriate artists / Italy / Capri Island / History; Expatriate authors / Italy / Capri Island / History; Expatriate artists; Expatriate authors; Intellectual life; Italy / Capri Island; History